Theories of Cause (Consideration) of Contract in the Serbian Doctrine of Civil Law After the Adoption of the Law on Obligations - Dudaš, Atila (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
The adoption of the Law on Obligations in 1978 can certainly be considered as an event of watershed importance in respect to the analysis of various theoretical points of view on the notion of cause (consideration) of contract in Serbian literature. The fact that it had not been explicitly regulated in Serbian positive law until the adoption of Law had a profound impact on the evolution of doctrine in this period. The range of differing theoretical points of view was very wide, covering essentially all the relevant streams in the doctrine of cause, from the ones accepting it (so-called causalistic theories), through the ones explaining it solely by the notion of exchange of assets (so-called economic theories), to the ones denying its legal significance in any sense (so-called anticausalistic theories). The most distinguished authorities in Serbian literature of contract law, who studied the notion of cause of contract in the period until the promulgation of the Law, were Dragoljub Aranđelović, Živojin Perić, Lazar Marković, Andrija Gams, Stevan Jakšić, Vladimir Kapor and Mihailo Konstantinović. The Law on Obligations explicitly regulates the notion of cause of contract as one of the preconditions of validity and effect of a contract, which had a substantial impact on the evolution of doctrine. On the one hand, being an institution of positive law, there is hardly an author who had not devoted some attention to the notion of cause of contract. In this paper the author analyzes the points of view of Stojan Cigoj, Ljubiša Milošević, Živomir Đorđević, Boris Vizner, Martin Vedriš, Želimir Šmalcelj, Jakov Radišić, Slobodan Perović, Jožef Salma and Oliver Antić. On the other hand, the scope of various, often conflicting, theories on cause of contract in Serbian literature shrank. One can recognize a tendency of abandonment of points of view disavowing any legal relevance of cause of contract and the majority of contemporary authorities argue that the cause of contract is a necessary legal institution, although they differ in the conceptual determination of this notion. However, Boris Vizner and Martin Vedriš may in this respect be deemed an exception. The former is of the opinion that the relevant sections of the Law on Obligations do not regulate the notion of cause of contract, but different titles of acquiring rights (titulus), while the latter claims that they mean the notion of basis of juridical act (Geschäftsgrundlage) from the German doctrine of civil law. All other authorities maintain that the sections of the Law on Obligations on the basis of obligation refer to the French notion of cause of contract and define it mainly within the premises of the neo-classical theory of cause of contract.